Penerapan Quality Function Deployment untuk Meningkatkan Kualitas Pelayanan Berdasarkan Kebutuhan Pelanggan Restoran Cepat Saji Omah Gedhi Steak dan Penyet di Kota Kendal - Fitri, Miladia Dliyaul; Cahya, Handy Nur (Jurnal Ekonomi dan Bisnis, 2023)
The population in this study were consumers of Omah Gedhi Steak and Penyet Fast Food Restaurants in Kendal City. The samples taken in this study used a purposive sampling technique, with as many as 100 respondents. The data analysis method used comes from primary data sources and additional (secondary) data as part of the Quality Function Deployment (QFD) process. The tests carried out are the Validity Test and Reliability Test using SPSS 24 assistance. Based on the data analysis carried out, conclusions were obtained using the Quality Function Deployment (QFD) method which uses a matrix from the House of Quality (HoQ) which can be used in answering the research questions. The Left Room of the House of Quality shows what are the priority needs of consumers namely the dimensions of "tangible", "reliability", "responsiveness", "assurance", "empathy". The Upper Room of the House of Quality reveals the Technical Response that can be carried out by the company, the company answers 14 attributes of the technical response shown in Table 4.9. The Lower Room is obtained from the sum of the value of the relationship between Consumer Needs and Technical Response, the first priority is occupied by "smile greetings" with a total of 64 point.Populasi dalam penelitian ini adalah konsumen Restoran Cepat Saji Omah Gedhi Steak dan Penyet di Kota Kendal. Sampel yang diambil dalam penelitian ini menggunakan teknik purposive sampling, dengan jumlah responden sebanyak 100 orang. Metode analisis data yang digunakan berasal dari sumber data primer dan data tambahan (sekunder) sebagai bagian dari proses Quality Function Deployment (QFD). Pengujian yang dilakukan adalah Uji Validitas dan Uji Reliabilitas menggunakan pendampingan SPSS 24. Berdasarkan analisis data yang dilakukan, diperoleh kesimpulan dengan menggunakan metode Quality Function Deployment (QFD) yang menggunakan matriks dari House of Quality (HoQ) yang dapat digunakan dalam menjawab pertanyaan penelitian. Ruang Kiri Rumah Berkualitas menunjukkan apa yang menjadi prioritas kebutuhan konsumen yaitu dimensi "tangible", "reliability", "responsiveness", "assurance", "empathy". Ruang Atas House of Quality menunjukkan Technical Response yang dapat dilakukan oleh perusahaan, perusahaan menjawab 14 atribut technical response yang ditunjukkan pada Tabel 4.9. Ruang Bawah diperoleh dari jumlah nilai hubungan antara Kebutuhan Konsumen dan Respon Teknis, prioritas pertama ditempati oleh "salam senyum" dengan total 64 poin.Keywords:Restaurant, Quality Function Deployment, House of Quality, Service Quality,Customer Needs.